Induction of cancer cell stemness by depletion of macrohistone H2A1 in hepatocellular carcinoma. Issue 2 (2nd January 2018) - Lo Re, Oriana; Fusilli, Caterina; Rappa, Francesca; Van Haele, Matthias; Douet, Julien; Pindjakova, Jana; Rocha, Sura Wanessa; Pata, Illar; Valčíková, Barbora; Uldrijan, Stjepan; Yeung, Raymond S.; Peixoto, Christina Alves; et al.
Abstract : Hepatocellular carcinomas (HCC) contain a subpopulation of cancer stem cells (CSCs), which exhibit stem cell–like features and are responsible for tumor relapse, metastasis, and chemoresistance. The development of effective treatments for HCC will depend on a molecular‐level understanding of the specific pathways driving CSC emergence and stemness. MacroH2A1 is a variant of the histone H2A and an epigenetic regulator of stem‐cell function, where it promotes differentiation and, conversely, acts as a barrier to somatic‐cell reprogramming. Here, we focused on the role played by the histone variant macroH2A1 as a potential epigenetic factor promoting CSC differentiation. In human HCC sections we uncovered a significant correlation between low frequencies of macroH2A1 staining and advanced, aggressive HCC subtypes with poorly differentiated tumor phenotypes. Using HCC cell lines, we found that short hairpin RNA–mediated macroH2A1 knockdown induces acquisition of CSC‐like features, including the growth of significantly larger and less differentiated tumors when injected into nude mice. MacroH2A1‐depleted HCC cells also exhibited reduced proliferation, resistance to chemotherapeutic agents, and stem‐like metabolic changes consistent with enhanced hypoxic responses and increased glycolysis. The loss of macroH2A1 increased expression of a panel of stemness‐associated genes and drove hyperactivation of the nuclear factor kappa B p65 pathway. Blocking phosphorylation of nuclear factor kappa B p65 on Ser536 inhibited the emergence of CSC‐like features in HCC cells knocked down for macroH2A1. Conclusion : The absence of histone variant macroH2A1 confers a CSC‐like phenotype to HCC cells in vitro and in vivo that depends on Ser536 phosphorylation of nuclear factor kappa B p65; this pathway may hold valuable targets for the development of CSC‐focused treatments for HCC. (Hepatology 2018;67:636‐650).